Interictal mood and personality disorders in temporal lobe epilepsy and juvenile myoclonic epilepsy. Issue 6 (December 1996) - Perini, G I; Tosin, C; Carraro, C; Bernasconi, G; Canevini, M P; Canger, R; Pellegrini, A; Testa, G
Abstract : BACKGROUND: Mood disorders have been described as the commonest psychiatric disorders in patients with temporal lobe epilepsy. Secondary depression in temporal lobe epilepsy could be interpreted either as an adjustment reaction to a chronic disease or as a limbic dysfunction. To clarify this issue, a controlled study of psychiatric disorders was conducted in different forms of epileptic and non-epileptic chronic conditions. METHODS: Twenty outpatients with temporal lobe epilepsy, 18 outpatients with juvenile myoclonic epilepsy–a primary generalised seizure disorder–20 matched type I diabetic patients, and 20 matched normal controls were assessed by a structured interview (SADS) and by self rating scales (Beck depression inventory (BDI) and the state and trait anxiety scales STAIX1 and STAIX2). RESULTS: Sixteen (80%) patients with temporal lobe epilepsy fulfilled the criteria for a psychiatric diagnosis at the SADS interview with a significantly higher frequency than patients with juvenile myoclonic epilepsy (22%) and diabetic patients (10%) (P < 0.0001). The most frequent disorder in temporal lobe epilepsy was a mood disorder: 11 (55%) patients with temporal lobe epilepsy had depression compared with three patients with juvenile myoclonic epilepsy and two diabetic patients (P < 0.001). Eight patients with temporal lobe epilepsy with an affective disorder also had a comorbid personality or anxiety disorder. Patients with temporal lobe epilepsy scored significantly higher on BDI, STAIX1, and STAIX2 than the three control groups (P < 0.001, P < 0.01, P < 0.001). CONCLUSIONS: Patients with temporal lobe epilepsy have a higher incidence of affective and personality disorders, often in comorbidity, than patients with juvenile myoclonic epilepsy and diabetic patients suggesting that these psychiatric disorders are not an adjustment reaction to a chronic disease but rather reflect a limbic dysfunction.